Residential care in California. Issue 1 (1st January 2020) - Frochen, Stephen; Rodnyansky, Seva; Ailshire, Jennifer
ABSTRACT: We examine the distribution of residential care in California, showing geographical disparities in care supply and need. We mapped the ratio of beds to older women in Los Angeles and San Diego County census tracts and concentrations of small and large facilities in the Cities of Los Angeles and San Diego. The largest ratios of residential care beds per older women occur on the border of the City of San Diego and on the periphery of Los Angeles County away from the City of Los Angeles. Clusters of small facilities take place in northern Los Angeles and southeastern San Diego, while clusters of large facilities occur in Downtown Los Angeles and near La Jolla. Understanding geographical disparities in residential care supply and need in California can help residential care developers, service providers, and local and state agencies partner in planning for residential care facility development in underserved areas.